CHARACTERISTICS OF MODULAR TEACHING TECHNOLOGY AND ITS USE IN TEACHING LITERATURE (Ustozlar uchun, 2025)
This work analyzes the possibilities of using modular teaching technology based on the lamb-drawing episode in The Little Prince. It emphasizes students’ return to the text, understanding the symbolic meaning through the episode, as well as differences in perception between children and adults. Through modules, students develop creative thinking, reasoning, and the ability to draw conclusions based on life experience. Furthermore, students are guided to form moral qualities by analyzing characters, symbols, and the text in literature lessons.